Assessment of residential defects at post-handover - Forcada, Nuria; Macarulla, Marcel; Love, Peter (American Society of Civil Engineers, 2013)
In Spain, the Ley de Ordenación de la Edificación (Building Regulation Act) has established compulsory warranties to ensure that buildings meet basic requirements with regard to functionality, general safety and structure, fireproofing, and use and habitability. Despite the requirements of this regulatory body, defects in newly built dwellings remain a pervasive problem, which has resulted in a plethora of complaints to the Instituto Nacional del Consumo (National Institute for Consumers' Protection), which deals with consumer protection in Spain. In this paper, a total of 2,351 post-handover defects derived from four Spanish builders and seven residential developments are classified according to their location, subcontract, and element. The research reveals that the most common defects identified by customers at handover were incomplete tile grouting and incorrect fixtures and fittings in toilets. In addition, failure to apply second coats of paint to walls was deemed a problematic issue. Typical surface/appearance defects were found to include floor or wall unevenness, stains, mess, and small cracks and marks, primarily caused by lack of protection. In areas where fixtures, fittings, and finishes were of a similar nature, such as the kitchen and bathroom, defect types also arose. Determining the location, subcontract, and element where defects occur in residential buildings can provide invaluable knowledge about areas where builders are likely to make errors or mistakes or take deliberate shortcuts during construction. Thus, emphasis on quality control and supervision of subcontract trades, especially in the identified areas, and during the final stages of residential construction, are critical to ensure that defects are reduced.